Contextualizing Multicultural Instruction in Indonesian EFL Classrooms: A Qualitative Case Study of Pedagogical Practices in Junior High Schools - Mohammad Rafi’i Mohammad Sata; Amirullah Abduh; Sultan Baa (Indonesian TESOL Journal, 2024)
This study explores how Multicultural Instruction (MI) is implemented in junior high school English classrooms. A pre-observation was conducted to identify whether multicultural elements had been integrated prior to the main observation phase. Using a qualitative case study approach, the research employed observation checklists to examine teacher activities in the classroom across two different schools. The findings reveal that MI has been implemented through five key dimensions: content integration, knowledge construction, prejudice reduction, equity pedagogy, and empowering classroom culture. However, the depth and mode of implementation vary between the two contexts. In SMPN 1 Tolitoli, MI is enacted through a more experiential, reflective, and student centered approach, where cultural content is deeply contextualized and connected to students’ lived experiences. whereas, SMPN 7 Tolitoli demonstrates a more structured and material-driven approach, emphasizing systematic instruction, guided analysis, and consistent classroom procedures. Despite these differences, both teachers successfully promote intercultural awareness, respect for diversity, and equitable participation. This study highlights that MI implementation is context-dependent and shaped by teachers’ pedagogical orientations, suggesting that both experiential and structured approaches can serve as complementary models in multicultural English language teaching. The findings contribute to the growing body of research on culturally responsive pedagogy by providing empirical insights from Indonesian EFL classrooms.